Nitrogen leaching and uptake from calcium cyanamide in comparison to urea and calcium ammonium nitrate in an utisol from the humid tropics - Pleysier, J.L.; Arora , Y.; Juo, A.S.R. (1987)
Leaching loss of N applied as calcium cyanamide (CaCN2 — 19% N), urea and calcium ammonium nitrate (CAN — 26% N) to a coarse textured, kaolinitic ultisol profile was studied in the laboratory using undisturbed soil columns. The soil columns were leached with an amount of water equivalent to the annual rainfall of the sampling site (2420mm) using a rainfall simulator over a period of 42 days. The ‘leachability’ of the three N fertilizers differed greatly and followed the order of CAN > urea > CaCN2. Most of the N lost through leaching was in NO3 form. Calcium cyanamide lost only 3% of applied N. Breakdown of CaCN2 to NH4 was incomplete (64%) and nitrification in the soil was inhibited resulting in negligible leaching loss. Nitrogen retained in the soil columns after the leaching cycle was mainly in ammoniacal form irrespective of source of N used. Effectiveness of CaCN2 as a N source was also studied in a greenhouse experiment with maize (Zea mays) and upland rice (Oryza sativa) as testing crops. Calcium cyanamide applied one week before sowing of crops was as effective as CAN and urea under conditions of no N leaching. When applied at the time of planting and two or more weeks before planting gave lower dry matter yields and N uptake than CAN and urea.